Dignity, fundamental rights and legal capacity: moving beyond the paradigm set by the General Comment on Article 12 of the Convention on the Rights of Persons with Disabilities. Issue 3 (1st September 2016) - Bilchitz, David
Abstract: Article 12 of the CRPD is often heralded as a 'paradigm shift' in the treatment of those with psychosocial disabilities. Historically, many persons with psychosocial disabilities have been treated as 'objects', without considering their expressions of will, even when they are capable of making decisions. That unacceptable status quo needed to change; yet, the shifts that have taken place – in a document such as the General Comment on Article 12 of the CRPD – actually reinforce the marginalisation of those with severe psychosocial disabilities and can harm their rights. The approach adopted in the General Comment does so, I argue, through reinforcing the traditional Kantian philosophical tradition which roots the very value and rights of individuals in their capacity to be autonomous agents in the world. That paradigm, unfortunately, is deeply flawed in its failure to take account of those who lack autonomous agency and other decision-making capacities, yet whose lives can go better or worse; and its failure to recognise and honour the value that lies in dependency and passivity as well as agency. I provide an alternative account which attempts to address these shortcomings and embrace the rights of those who are dependent on care and largely passive whilst not diminishing the importance of autonomy and agency for others. I argue that South Africa should not follow the approach of the General Comment where it would jeopardise the rights of those with psychosocial disabilities and, instead, should, in its laws, give expression to the more normatively desirable approach articulated in this article.